Secret reports on Nazi Germany : the Frankfurt School contribution to the war effort - Neumann, Franz L. (Franz Leopold), 1900-1954 (Princeton University Press, 2013)
During the Second World War, three prominent members of the Frankfurt School--Franz Neumann, Herbert Marcuse, and Otto Kirchheimer--worked as intelligence analysts for the Office of Strategic Services, the wartime forerunner of the CIA. This book brings together their most important intelligence reports on Nazi Germany, most of them published here for the first time. These reports provide a fresh perspective on Hitler's regime and the Second World War, and a fascinating window on Frankfurt School critical theory. They develop a detailed analysis of Nazism as a social and economic syst.